Activation of pyruvate dehydrogenase by dichloroacetate has the potential to induce epigenetic remodeling in the heart. (May 2015) - Matsuhashi, Tomohiro; Hishiki, Takako; Zhou, Heping; Ono, Tomohiko; Kaneda, Ruri; Iso, Tatsuya; Yamaguchi, Aiko; Endo, Jin; Katsumata, Yoshinori; Atsushi, Anzai; Yamamoto, Tsunehisa; Shirakawa, Kohsuke; et al.
Abstract: Dichloroacetate (DCA) promotes pyruvate entry into the Krebs cycle by inhibiting pyruvate dehydrogenase (PDH) kinase and thereby maintaining PDH in the active dephosphorylated state. DCA has recently gained attention as a potential metabolic-targeting therapy for heart failure but the molecular basis of the therapeutic effect of DCA in the heart remains a mystery. Once-daily oral administration of DCA alleviates pressure overload-induced left ventricular remodeling. We examined changes in the metabolic fate of pyruvate carbon (derived from glucose) entering the Krebs cycle by metabolic interventions of DCA. 13 C6 -glucose pathway tracing analysis revealed that instead of being completely oxidized in the mitochondria for ATP production, DCA-mediated PDH dephosphorylation results in an increased acetyl-CoA pool both in control and pressure-overloaded hearts. DCA induces hyperacetylation of histone H3K9 and H4 in a dose-dependent manner in parallel to the dephosphorylation of PDH in cultured cardiomyocytes. DCA administration increases histone H3K9 acetylation in in vivo mouse heart. Interestingly, DCA-dependent histone acetylation was associated with an up-regulation of 2.3% of genes (545 out of 23, 474 examined). Gene ontology analysis revealed that these genes are highly enriched in transcription-related categories. This evidence suggests that sustained activation of PDH by DCA results in an overproduction of acetyl-CoA, which exceeds oxidation in the Krebs cycle and results in histone acetylation. We propose that DCA-mediated PDH activation has the potential to induce epigenetic remodeling in the heart, which, at least in part, forms the molecular basis for the therapeutic effect of DCA in the heart. Highlights: Dichloroacetate (DCA) promotes pyruvate entry into the Krebs cycle. DCA exerts an anti-remodeling effect on the left ventricle under pressure-overload. DCA induces an overproduction of acetyl-CoA, which results in histone acetylation. Histone acetylation was associated with an up-regulation of 2.3% of genes. These genes are highly enriched in categories related to transcriptional processes.